KINERJA PUSTAKAWAN LAYANAN SIRKULASI DALAM MEMANFAATKAN SENAYAN LIBRARY MANAGEMENT SYSTEM (SLiMS) - Ridwan, Parid; Sudarsana, Undang; Rahmatulloh, Tansah (Nusantara Journal of Information and Library Studies (N-JILS), 2021)
This study aims to determine the performance of librarians in terms of knowledge, skills, attitudes, and obstacles faced by librarians in utilizing SLiMS at UPT Pasundan University Library, Bandung. The method used in this research is qualitative method. Data collection techniques through observation, interviews, and documentation studies. Informants in this study amounted to two people who are librarians of circulation services. The data analysis technique uses data collection, data reduction, data presentation, and drawing conclusions. The results showed that first, the knowledge and understanding of librarians in utilizing SLiMS can be said to be good. Although librarians only know the role of SLiMS in completing their work. Whereas SLiMS can be used in planning the work to be done by the librarian. Second, the skills of circulation service librarians in utilizing SLiMS can be said to be skilled. This can be seen from the ability of librarians to use various features available in SLiMS for borrowing, returning, extending, fines and other activities related to activities in library circulation services. Third, the attitude of the circulation service librarian in utilizing SLiMS can be said to be good. This can be seen from the ease of completing work and satisfaction with the work that has been completed by the librarian. Fourth, the obstacles experienced by circulation service librarians in utilizing SLiMS are difficulties in installing and migrating data to SLiMS because the software previously used was different.Keywords: performance; librarian; senayan library management systemABSTRAKPenelitian ini bertujuan untuk mengetahui kinerja pustakawan dilihat dari aspek pengetahuan, keterampilan, sikap, dan hambatan yang dihadapi pustakawan dalam memanfaatkan SLiMS di UPT Perpustakaan Universitas Pasundan Bandung. Metode yang digunakan dalam penelitian ini adalah metode kualitatif. Teknik pengumpulan data melalui observasi, wawancara, dan studi dokumentasi. Informan dalam penelitian ini berjumlah dua orang yang merupakan pustakawan bagian layanan sirkulasi. Tekink Analisa data menggunakan pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan, bahwa pertama, pengetahuan dan pemahaman pustakawan dalam memanfaatkan SLiMS dapat dikatakan baik. Meskipun pustakawan hanya mengetahui peran SLiMS dalam menyelesaikan pekerjaan mereka. Padahal SLiMS bisa digunakan dalam merencanakan pekerjaan yang akan dikerjakan oleh pustakawan. Kedua, Keterampilan pustakawan layanan sirkulasi dalam memanfaatkan SLiMS dapat dikatakan terampil. Hal ini terlihat dari mampunya pustakawan dalam menggunakan berbagai fitur yang ada pada SLiMS untuk kegiatan peminjaman, pengembalian, perpanjangan, denda dan lain sebagainya yang berkaitan dengan kegiatan pada layanan sirkulasi perpustakaan. Ketiga, sikap pustakawan layanan sirkulasi dalam memanfaatkan SLiMS dapat dikatakan baik. Hal ini terlihat adanya kemudahan dalam menyelesaikan pekerjaan dan kepuasan akan pekerjaan yang sudah diselesaikan oleh pustakawan. Keempat, hambatan yang dialami oleh pustakawan layanan sirkulasi dalam memanfaatkan SLiMS adalah kesulitan dalam menginstal dan melakukan migrasi data ke SLiMS dikarenakan software yang sebelumnya digunakan berbeda.